The Role of Pentagon Fraud in Detecting Fraudulent Financial Statements - Rimadanti, Shevina; Santoso, Aprih; Sulistyawati, Ardiani Ika (Manunggal Halim Jaya, 2022)
Pentagon fraud is one type of financial fraud that occurs in companies. Pentagon fraud occurs when a company hides or deceives financial statements to reduce the amount of taxes it must withhold or to increase the value of the company for investors report. The purpose of this study was to examine and analyze the effect of the pentagon fraud variable on financial statement fraud with the dependent variable proxy being F-Scores. While the independent variables used in this study are financial stability (ACHANGE), financial target (ROA), nature of industry (RECEIVABLE), ineffective monitoring (BDOUT), change in auditor (CPA), change in directors (DCHANGE), and the frequent number of the CEO's picture (CEOPIC). This research use samples of consumption sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2016–2020. By using purposive sampling, there are 55 samples from 11 companies. The data analysis method used multiple linear regression analysis, with hypothesis testing t-test, f-test, descriptive test, coefficient of determination. The results of this research shows that financial stability, ineffective monitoring, change in auditor, and change in direction have no significant influence on financial fraud statements. But financial target, nature of industry, and frequent number of CEO's picture have significant influence on financial fraud statement.